2019
DOI: 10.1016/j.buildenv.2019.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the accuracy on PMV – PPD model using the ASHRAE Global Thermal Comfort Database II

Abstract: The predicted mean vote (PMV) and predicted percentage of dissatisfied (PPD) are the most widely used thermal comfort indices. Yet, their performance remains a contested topic. The ASHRAE Global Thermal Comfort Database II, the largest of its kind, was used to evaluate the prediction accuracy of the PMV/PPD model. We focused on: (i) the accuracy of PMV in predicting both observed thermal sensation (OTS) or observed mean vote (OMV) and (ii) comparing the PMV-PPD relationship with binned OTS -observed percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 328 publications
(157 citation statements)
references
References 36 publications
7
117
0
Order By: Relevance
“…The PMV model has its highest prediction accuracy in the thermal neutral zone and it decays towards the extremes of thermal sensation scale [16]. We showed that personal thermal comfort models using wearable sensors do exactly the opposite.…”
Section: Comparison Of Prediction Power For Different Thermal Sensatimentioning
confidence: 82%
See 2 more Smart Citations
“…The PMV model has its highest prediction accuracy in the thermal neutral zone and it decays towards the extremes of thermal sensation scale [16]. We showed that personal thermal comfort models using wearable sensors do exactly the opposite.…”
Section: Comparison Of Prediction Power For Different Thermal Sensatimentioning
confidence: 82%
“…The models were trained on the entire dataset of all the 14 subjects instead of each subject and then averaged. In general, applying each individual feature or feature combinations generates a prediction power greater than the conventional PMV/adaptive model that has a very low prediction power on thermal preference (AUC≈0.5) [16,26].…”
Section: Importance Of Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations of thermal sensations are commonly done by Fanger's energy balance models. 13 However, more recent experimental studies have shown that observed and calculated values might differ considerably [14][15][16][17][18] leading to the development of theories explaining the differences according to factors such as "short-term thermal adaptation" and "thermal expectation." 19 Additionally, thermal sensation of females and males in the same thermal environment, activity, and clothing insulation has been reported as being consistently different.…”
Section: Theory and Aimmentioning
confidence: 99%
“…Calculations of thermal sensations are commonly done by Fanger's energy balance models . However, more recent experimental studies have shown that observed and calculated values might differ considerably leading to the development of theories explaining the differences according to factors such as “short‐term thermal adaptation” and “thermal expectation.”…”
Section: Introductionmentioning
confidence: 99%